Polymer composites in the aerospace industry - Irving, E.; Soutis, C. (Woodhead Publishing, 2015)
"Polymer composites are increasingly used in aerospace applications due to properties such as strength and durability compared to weight. Edited by two leading authorities in the field, this book summarises key recent research on design, manufacture and performance of composite components for aerospace structures. Part one reviews the design and manufacture of different types of composite component. Part two discusses aspects of performance such as stiffness, strength, fatigue, impact and blast behaviour, response to temperature and humidity as well as non-destructive testing and monitoring techniques."-- Unedited summary from book
Keywords: Composite materials.; Space vehicles -- Materials.; Aerospace engineering.; elektronické knihy; electronic books